Analisis Pengaruh Inflasi, Nilai Tukar Dan Bi Rate Terhadap Tabungan Mudharabah Pada Perbankan Syariah Di Indonesia - Zakaria Batubara; Eko Nopiandi (LPPM ISNJ Bengkalis, 2020)
This research aims to determine the effect of inflation, exchange rates, and the BI Rate on mudharabah savings in Islamic banking in Indonesia partially and simultaneously. This research is a quantitative study with time-series data. The data used in this study are secondary data. The population in this study is inflation data, the rupiah exchange rate, and the BI Rate and mudharabah savings. The population of Islamic banks in this study totalled 34 Islamic banks. The data analysis technique used in this study is the multiple regression analysis. Partially, inflation, exchange rates or the rupiah exchange rate and the BI Rate have a positive effect on mudharabah savings in Islamic banking in Indonesia. Simultaneously the inflation variable, the exchange rate or the rupiah exchange rate and the BI Rate have a significant effect on mudharabah savings in Islamic banking in Indonesia with an influence of 88.6%.